Reading Habits and Academic Performance of College-Level Students - Manandhar, Raju Bhai; Timilsina, Jagat; Shrestha, Purna Man; Manandhar, Eirika (Journal of Nepalese Management Academia, 2024)
The objective of the study is to examine the effect of reading habits on the academic performance of college-level students. Descriptive and causal research designs were adopted to deal with various issues in the study. The study adopted an online survey to collect primary data. The study targeted college-level students of Kathmandu Valley. 342 students have been selected through judgmental sampling. A structural questionnaire link using ‘Google Forms’ was sent to students through WhatsApp, Facebook, and email. Out of 390, a total of 342 students provided complete information regarding the survey. Various statistical tools were employed in the study such as frequency, percentage, mean, correlation, regression, etc., The study found that there is a strong relationship between reading habits and the academic performance of college level students. The study also showed that reading habits have a positive and significant effect on the academic performance of college-level students. Similarly, gender does not affect reading habits but affects academic performance. As a result, reading plays an important role in the lives of students. Academic institutions must prioritize creating supportive environments such as well-equipped libraries, accessible reading resources, and study-friendly spaces to cultivate consistent reading behaviour, and teachers should play a more significant role in motivating students to read.